Plataiai Archäologie und Geschichte einer boiotischen Polis - Konecny, Andreas (Österreichisches Archäologisches Institut, 2013)
Plataiai, in SW-Boiotia, is famous above all for the events which took place in its vicinity in the autumn of 479 B.C. This victory of the Greeks over the Persian army, in concert with the Battle of Salamis, was an event of the utmost significance for European history and is often the topic of modern scientific analysis. Nevertheless, the ancient polis which gave its name to the battle has been overlooked by modern historians and all the more by archaeologists, in a rather curious way. The Plataiai Project was consequently inaugurated in 1996 in order to gain a better understanding of the history and chronology of this ancient place. Results from the investigations have made it possible to establish a settlement sequence for Plataiai; this sequence spans seven millennia, from the Middle Neolithic Age to the modern era. Plataiai is situated in a relatively secure location on the lower slopes of Mt. Kithairon where the first settlers established a small hamlet. The site continued to be inhabited in a nearly unbroken sequence into historical times. During the formative period of Classical Hellas Plataiai developed into an independent polis. The town became entangled in the internecine struggles of 6th and 5th century B.C. Greece and suffered accordingly. Plataiai was twice destroyed and depopulated as a result of the wars between Athens, Sparta and Thebes. Only a final shift of the political and strategic focusses under Philip and Alexander helped secure the existence of the town. During Hellenistic times and the time of the Roman Empire Plataiai remained undisturbed. Plataiai's existence during the 6th, 5th and 4th centuries B.C. is documented mainly by way of surface finds and its earliest known fortification. In addition to the discovery of fragmentary dwellings from the 6th century B.C., small scale excavations appear to have uncovered a cult deposit from the same period. The main characteristics of Plataiai in the late 4th century B.C. and beyond consist of an ambitious extension of the settlement, structured internally along an orthogonal grid of urban blocks and roads which was protected by an extended belt of fortifications. Geophysical survey has helped to locate and document the main urban monuments, such as the Agora, the precinct of Dionysos, the Temple of Hera, and other public buildings, in addition to an extended area covered by private dwellings, some of truly impressive size. The evidence of such large buildings confirms, beyond a doubt, that several very wealthy families existed in Plataiai, who made good use of their dwellings to express their social and political status. Late Antiquity seems to have severely curtailed Plataiai's prosperity. Urgent military threats led to the building of an emergency fortification which re-used the building materials of many Hellenistic and Roman structures. Nevertheless, a bishopric at Plataiai, a note in Procopius' de aedeficiis and the remains of several churches at the site prove that the town still existed during the reign of the emperor Justinian, whereas it is possible that the site was abandoned after this time. Only from the 11th and 12th centuries A.D. onwards does the surface material again corroborate the existence of a settlement at the site. The modern village of Kokla was renamed Plataies during the 1920s and thus continues the tradition of the ancient polis right into the 21st century A.D.